1999
DOI: 10.1097/00001756-199904060-00001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium on methamphetamine-induced regional Fos protein expression in the rat brain

Abstract: Lithium has been used widely for the treatment of manic states. Since amphetamines produce effects in humans similar to the symptoms of idiopathic mania, amphetamine administration to animals has been proposed as a model of this condition. To investigate the neurobiologic substrates of the antimanic effects of chronic lithium administration, we investigated its effects on methamphetamine-induced regional Fos protein expression in the rat brain. Chronic lithium administration (14 days; serum lithium concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
1
10
1
3
Order By: Relevance
“…In contrast, our previous study (Lee et al 1999) showed that lithium treatment significantly reduced the number of these neurons in the prefrontal cortex and the central amygdaloid nucleus, as well as in the nucleus accumbens and the caudate/putamen. Thus, the core of the nucleus accumbens and the caudate/putamen are common target regions in which both CBZ and lithium treatments suppress methamphetamine-induced Fos expression.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…In contrast, our previous study (Lee et al 1999) showed that lithium treatment significantly reduced the number of these neurons in the prefrontal cortex and the central amygdaloid nucleus, as well as in the nucleus accumbens and the caudate/putamen. Thus, the core of the nucleus accumbens and the caudate/putamen are common target regions in which both CBZ and lithium treatments suppress methamphetamine-induced Fos expression.…”
Section: Discussioncontrasting
confidence: 81%
“…Thus, the core of the nucleus accumbens and the caudate/putamen are common target regions in which both CBZ and lithium treatments suppress methamphetamine-induced Fos expression. In these regions, chronic lithium administration significantly attenuates the number of methamphetamine-induced Fos-LI-positive neurons by approximately 40-65% (Lee et al 1999), and chronic CBZ administration significantly attenuates it by approximately 32-39% (Table 1). The caudate/putamen (especially the medial section) and the nucleus accumbens are closely related to emotion and serve as output organs of reward to the motor system (Fibiger and Phillips 1986;Mogenson et al 1980;Robbins and Everitt 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute methamphetamine injection has been shown to induce c-Fos protein expression in the central and medial (480) or in the central and basolateral nuclei (265,266). In all these studies, other amygdalar nuclei were not analyzed.…”
Section: Amphetamines and C-fos Expressionmentioning
confidence: 99%
“…For example, the acute administration of MA to rodents resulted in production of oxidative stress as demonstrated by reduced glutathione and increased oxidized glutathione levels in the rat striatum and prefrontal cortex (Acikgoz et al 1998, Harold et al 2000. MA induced oxidative stress in mice has also been observed to activate redox-responsive transcription factors such as activator protein-1 (AP-1) and cAMPresponsive element binding protein (CREB) (Lee et al 1999).…”
Section: Methamphetamine Neurotoxicitymentioning
confidence: 99%